Critical discourse for social integration of children with disabilities within the context of human rights - Acienė, Elvyra; Vaičekauskaitė, Rita (Social Welfare: Interdisciplinary Approach, 2011)
The process of social integration of the people with disabilities has already been implemented for two decades in Lithuania. However, Ruškus and Mažeikis (2007) note, that only critical analysis of ideas of social integration of the people with disabilities helps to determine whether the situation of the people with disabilities in nowadays Lithuania is changing essentially or merely formally. While analyzing the educational system in Lithuania little attention is paid to the change of the system in the perspective of human rights. From the point of view of Oliver (1996), talking about the social integration of the people with disabilities fi rst of all means talking about human rights. Rix and co-authors (2010) note that human rights being universal are inseparable reference to social integration. The authors mentioned above reveal that talking about human rights has an emancipating power for the groups of society that undergo social exclusion. The education system often creates limitations for social integration of the people with disabilities, indicating the limited opportunities of the children with disabilities to achieve academic success. Human rights are the system of values and ideas, which refers to the desire to eliminate conflicts and reconcile opposites. Speaking about human rights is very important, because the idea of social integration of the people with disabilities in Western Europe and the USA began with the human rights movement in the middle of the 20th century. Ife (2001) prompts people of various professions and social statuses to discuss human rights actively; otherwise human rights remain only a formal declaration. The daily theoretical and practical talk about children’s rights is very important, because violations of children’s rights are not readily visible.
Keywords: discourse; disability; social integration; human rights; children’s rights